2018
DOI: 10.1103/physreva.97.052128
|View full text |Cite
|
Sign up to set email alerts
|

Entropic no-disturbance as a physical principle

Abstract: The celebrated Bell-Kochen-Specker no-go theorem asserts that quantum mechanics does not present the property of realism, the essence of the theorem is the lack of a joint probability distributions for some experiment settings. In this work, we exploit the information theoretic form of the theorem using information measure instead of probabilistic measure and indicate that quantum mechanics does not present such entropic realism neither. The entropic form of Gleason's no-disturbance principle is developed and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…This has crucial applications in our understanding of Bell nonlocality and quantum contextuality [22][23][24][25][26], for which the local (non-contextual) hidden variable (LHV/NCHV) model is proved to be equivalent to a joint probability model. The existence of LHV/NCHV models can be turned into a classical marginal problem [25,27,[38][39][40].…”
Section: Marginal Problemmentioning
confidence: 99%
“…This has crucial applications in our understanding of Bell nonlocality and quantum contextuality [22][23][24][25][26], for which the local (non-contextual) hidden variable (LHV/NCHV) model is proved to be equivalent to a joint probability model. The existence of LHV/NCHV models can be turned into a classical marginal problem [25,27,[38][39][40].…”
Section: Marginal Problemmentioning
confidence: 99%
“…The phenomenon is now known as monogamy of quantum correlations. It's shown that there exist monogamy relations for Bell nonlocality [24][25][26][27][28], quantum steering [29], and entanglement [17,30,31]. In this section, we study the monogamy equalities of entanglement restricted by quantum geometric invariance.…”
Section: Quantum Geometric Invariance and Entanglement Distributionmentioning
confidence: 99%